Answer:
Step-by-step explanation:
As it is a second order equation, it means that it has two possible answers and they are
and
.
The famous quadratic formula for solving any second order equation is the following:
![x_{1} = \frac{-b + \sqrt{b^2 - 4 ac}}{2a}\\x_{2}=\frac{-b - \sqrt{b^2 - 4 ac}}{2a}](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%20%5Cfrac%7B-b%20%2B%20%5Csqrt%7Bb%5E2%20-%204%20ac%7D%7D%7B2a%7D%5C%5Cx_%7B2%7D%3D%5Cfrac%7B-b%20-%20%5Csqrt%7Bb%5E2%20-%204%20ac%7D%7D%7B2a%7D)
Where a is the coefficient of
, b is the coefficient of x, and c is the free term. In other words,
![a = 3\\b=4\\c=-2](https://tex.z-dn.net/?f=a%20%3D%203%5C%5Cb%3D4%5C%5Cc%3D-2)
as the equation should be in the following form:
![a x^2 + bx+c = 0](https://tex.z-dn.net/?f=a%20x%5E2%20%2B%20bx%2Bc%20%3D%200)
Therefore the possible answer should be the following,
![\frac{-4 + \sqrt{4^2 - 4*3*(-2)}}{2*3}=\frac{-4 +\sqrt{16 + 24}}{6} =\frac{-4 + \sqrt{40}}{6}=\\ \frac{-4 + \sqrt{4*10}}{6} = \frac{-4 + 2\sqrt{10}}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%20%2B%20%5Csqrt%7B4%5E2%20-%204%2A3%2A%28-2%29%7D%7D%7B2%2A3%7D%3D%5Cfrac%7B-4%20%2B%5Csqrt%7B16%20%2B%2024%7D%7D%7B6%7D%20%3D%5Cfrac%7B-4%20%2B%20%5Csqrt%7B40%7D%7D%7B6%7D%3D%5C%5C%20%5Cfrac%7B-4%20%2B%20%5Csqrt%7B4%2A10%7D%7D%7B6%7D%20%3D%20%5Cfrac%7B-4%20%2B%202%5Csqrt%7B10%7D%7D%7B6%7D)
![\frac{2*(-2 + \sqrt{10})}{2*3} = \frac{-2 + \sqrt{10}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%2A%28-2%20%2B%20%5Csqrt%7B10%7D%29%7D%7B2%2A3%7D%20%3D%20%5Cfrac%7B-2%20%2B%20%5Csqrt%7B10%7D%7D%7B3%7D)
by dividing the numerator and denominator by 2, we can deduce the following,
Answer:
x = 10
Step-by-step explanation:
Since the triangle is right use the sine ratio to find x
sin30° =
=
cross- multiply
x × sin30° = 5 ( sin30° = 0.5 )
0.5x = 5 ( divide both sides by 0.5 )
x = 10
if there are 300 raffle tickets and one raffle ticket is drawn, the proabability of drawing the next one is 1 in 299 because there is one less ticket from the previous win
Answer:
The answer is -2
Step-by-step explanation:
slope = y2-y1/x2-x1
= -6-6/3-(-3)
= -12/3+3
= -12/6
= -2
Answer:
you would get your answer by timesing all the numbers together, that it gives you.
Step-by-step explanation:
If my math is correct it would be the second one.